DEVELOPMENT OF REGISTRATION AND AUTHENTICATION SYSTEMS FOR A WEB APPLICATION (Modern information system and technologies, 2018)
This article describes the process of developing a registration and authentication systems for a Web application based on ReactJS, NodeJS, MongoDB. This system can be used in different types of applications, easily scalable and has the ability to easily extend its functionality by installing additional modules.